Dimensi Kekontekstualan Materi Buku Basa Jawa Trampil ing Basa Trapsila ing Bawa (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2022)
Textbooks must comply with the BSNP assessment criteria, one of which is the contextual dimension. Overall, the Javanese language textbook entitled Basa Jawa Trampil ing Basa Trapsila ing Bawa which is used in SMP Negeri 1 Ngawi was not in accordance with the real-life context in Ngawi Regency. This study aims to describe the contextual form of the material in the Basa Jawa Trampil ing Basa Trapsila ing Bawa textbook. A descriptive qualitative approach is used as a research approach. The data collection technique is reading, sorting, and note-taking techniques. The source of the research data was Basa Jawa Trampil ing Basa Trapsila ing Bawa textbook. The research instrument used data cards. The data validation technique used triangulation of data sources. Based on the results of the contextual analysis of place and environment, the six materials contained in the book are in accordance with the benchmarks for the contextuality of place and environment and found 21 data in the form of one picture and 20 quotes. In the contextual context, five pieces of data were found in the form of four quotations and one picture, while in the environmental context, that divided into three spheres; the personal sphere (six quotations), the social sphere (six quotations), and the cultural sphere (four quotations). It is sufficient to say that this book is contextually based on Ngawi Regency because it provides various materials that are in accordance with the contextual indicators of place and environment materials.